2007
DOI: 10.1002/jmv.20877
|View full text |Cite
|
Sign up to set email alerts
|

Determining the source of nosocomial transmission in hemodialysis units in Tunisia by sequencing NS5B and E2 sequences of HCV

Abstract: Hepatitis C virus infection is a significant problem in hemodialysis units. HCV is very variable genetically with six genotypes. Clinical and epidemiological investigation of a new infection requires the determination of both the genotype and the strain of the HCV involved. A prospective, epidemiologic study of 395 dialysis patients in Tunisia was conducted from November 2001 to November 2003 to identify the source of nosocomial transmission using phylogenetic analysis of NS5b and E2 sequences. Hepatitis C inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 27 publications
0
11
1
Order By: Relevance
“…To detect possible intra‐unit HHV‐8 transmission in patients with chronic renal failure, the hypervariable region (K1/V1) was analyzed and compared between patients undergoing hemodialysis. Previous studies have documented intra‐unit hepatitis C virus transmission in hemodialysis units, with phylogenetic analysis revealing clustering between patients who were dialyzed during the same shift and in the same area [Hmaied et al, 2007]. In the current study, however, phylogenetic analysis revealed that none of the HHV‐8‐infected patients with chronic renal failure carried identical K1/V1 sequences.…”
Section: Discussioncontrasting
confidence: 55%
“…To detect possible intra‐unit HHV‐8 transmission in patients with chronic renal failure, the hypervariable region (K1/V1) was analyzed and compared between patients undergoing hemodialysis. Previous studies have documented intra‐unit hepatitis C virus transmission in hemodialysis units, with phylogenetic analysis revealing clustering between patients who were dialyzed during the same shift and in the same area [Hmaied et al, 2007]. In the current study, however, phylogenetic analysis revealed that none of the HHV‐8‐infected patients with chronic renal failure carried identical K1/V1 sequences.…”
Section: Discussioncontrasting
confidence: 55%
“…Of the 96 strains, 95 (99%) were genotype 4 while the remaining one was genotype 1. The NS5B region is commonly analysed to distinguish between related and unrelated isolates of the same subtypes especially in HCV nosocomial transmission that occurred over a period of several years 2123. This region is known to be stable over time24 and was recommended for the study of ancient HCV transmission events 25.…”
Section: Methodsmentioning
confidence: 99%
“…[23][24][25][26][27][28] However, the phylogenetic analysis of a fragment from the virus isolates has provided an important tool in establishing genetic relatedness of viruses, [29][30][31] which has been proven to be successful for the study of the different routes of transmission. 9,28,[30][31][32][33] The results of the sequence analysis in this study showed that the sequence identity values from family pairs were not higher than that of unrelated subjects. Kimura distances from family pairs were also not shorter than that of unrelated subjects.…”
Section: Discussionmentioning
confidence: 48%